In pursuit of neuroimaging biomarkers to guide treatment selection in major depressive disorder: a review of the literature. (8th April 2015) - Lener, Marc S.; Iosifescu, Dan V.
Abstract : Over the last few decades, neuroimaging techniques have advanced the identification of structural, functional, and neurochemical brain abnormalities that are associated with the increased risk, clinical course, and treatment outcomes of major depressive disorder (MDD). This paper reviews specific neuroimaging abnormalities that, on the basis of early studies, may discriminate between MDD patients who do or do not respond to current therapeutic modalities, such as antidepressants, cognitive behavioral therapy, or novel therapies. Differences in gray matter volume, white matter coherence, brain activity via structural and functional magnetic resonance imaging techniques, and concentrations of specific brain metabolites (as measured with magnetic resonance spectroscopy), are potential biomarkers discussed in this review. Given the heterogeneity of MDD, larger, multisite studies with increased statistical power will be needed to identify more precise imaging biomarkers of treatment response in MDD.